"Ciprofloxacin-induced" bilateral quadriceps tendon rupture: A case report and conclusions of the recent literature. (April 2021) - Suter, Cyrill; Leemann, Harald; Twerenbold, Reto
Abstract: The potential risk of fluoroquinolones on the musculoskeletal tissue, and tendinous structures in particular, has been known since its introduction in the 1980s. Following reports of serious and persistent side effects in their national registry, the German medicines authority (BfArM) has requested the European Medicines Agency (EMA) to conclude a safety review focusing on long-lasting effects mainly affecting the musculoskeletal and nervous systems. This review, published in early 2019, led to restriction of the usage of fluoroquinolones due to the risk of disabling and potentially long-term side effects. Furthermore, there have been a number of meta-analyses published in the recent years, which brought more clarity to the extent of fluoroquinolones' possible side effects. With this case report followed by an overview of the latest evidence, we would like to highlight these latest efforts in the quest to prescribe fluoroquinolones cautiously and sensitize physicians to this topic.